Toxicokinetic and Genotoxicity Study of NNK in Male Sprague Dawley Rats Following Nose-Only Inhalation Exposure, Intraperitoneal Injection, and Oral Gavage. (3rd May 2021) - Hu, Shu-Chieh; Bryant, Matthew S; Sepehr, Estatira; Kang, Hyun-Ki; Trbojevich, Raul; Lagaud, Guy; Mehta, Darshan; Ding, Wei; Mittelstaedt, Roberta A; Pearce, Mason G; Bishop, Michelle E; Davis, Kelly J; et al.
Abstract: The tobacco-specific nitrosamine NNK [4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone] is found in tobacco products and tobacco smoke. NNK is a potent genotoxin and human lung carcinogen; however, there are limited inhalation data for the toxicokinetics (TK) and genotoxicity of NNK in vivo . In the present study, a single dose of 5 × 10 −5, 5 × 10 −3, 0.1, or 50 mg/kg body weight (BW) of NNK, 75% propylene glycol (vehicle control), or air (sham control) was administered to male Sprague-Dawley (SD) rats (9–10 weeks age) via nose-only inhalation (INH) exposure for 1 h. For comparison, the same doses of NNK were administered to male SD rats via intraperitoneal injection (IP) and oral gavage (PO). Plasma, urine, and tissue specimens were collected at designated time points and analyzed for levels of NNK and its major metabolite 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL) and tissue levels of DNA adduct O 6 -methylguanine by LC/MS/MS. TK data analysis was performed using a non-linear regression program. For the genotoxicity subgroup, tissues were collected at 3 h post-dosing for comet assay analysis. Overall, the TK data indicated that NNK was rapidly absorbed and metabolized extensively to NNAL after NNK administration via the three routes. The IP route had the greatest systemic exposure to NNK. NNK metabolism to NNAL appeared to be more efficient via INH than IP or PO. NNK induced significant increases in DNA damage in multiple tissues via the three routes. The results of this study provide new information and understanding of the TK and genotoxicity of NNK.